Narcisismo e imagem corporal: considerações sobre a vivência da amputação - Friggi, Priscila Ferreira (2015)
This study aimed to understand the meanings of people submitted to limb amputation surgery attributed to body change process, based on the psychoanalytic theory. For that, we sought identify the specifically relation between amputation surgery and narcissism, as well as describe how is the articulation of this procedure and the body image. To activate the objectives, we choose qualitative research, with descriptive and exploratory approach. For data collection was used semi-structured interviews with 9 people who did limb amputation surgery and had medical monitoring in a Rio Grande do Sul s public hospital. The data collected were analysed by Bardin s Content Analysis and, all that were in agreement of this technique were listed in 5 repetition categories, showed in the results of this study. It was found that limb amputation was a traumatic event for the interviewed people, motivating an abrupt break in their symbolic constructive base, threatening them. This threat reflected directly in body image and narcissism, and they needed a grief process for the lost member and the body image that they had until that moment in order that happen the new body reintegration process. This grief process was essential for building new body s auto image, that is a basis for the narcissist action of body unification. Although, the grief process that isn t satisfactory is harmful for the restructuration self-image process, and can turn this process like a dead of the limb amputated. Then, this study concluded that limb amputation people can reframe your body even with the absence of a member and experience the potential and possibilities that this body still has.